Soft topological approaches via soft γ-open sets - Samirah Alzahrani; A. A. Nasef; N. Youns; A. I. EL-Maghrabi; M. S. Badr (AIMS Mathematics, 2022)
The purpose of this research is to present, study, and prove numerous features of soft γ-open (Sγo) and soft γ-closed (Sγc) sets in soft topological structure (Sτs). Also, we show that the collection of Sγo sets is a soft supra topology (Ssτ) by stating and proving the conditions. Finally, we study soft γ-continuous functions and soft γ-irresolute functions. Some related properties of these new soft of discussed with help of some examples.